Socialization of the Importance of Knowledge about Speech Disorders in Early Childhood - Rahmi Khalida; Deli Natalia (Global Health Science Group, 2020)
Parents take a very big share in their children's education, because the original parents formed the family. During visits to partner schools, several problems were identified after conducting observations and interviews with teachers and parents of guardians Mutathahirin Lubuk Lintah Similar Early Childhood Education Unit. The solution offered to this problem is to socialize to parents and teachers about the importance of knowledge of language and speech disorders in early childhood Mutathahirin Lubuk Lintah Similar Early Childhood Education Unit Kuranji district Padang city Sumatera Barat province. This activity was carried out using the lecture and discussion method on Tuesday, May 28, 2019. Participants in the socialization activities were 17 parents, 2 PAUD teachers and 17 students Mutathahirin Lubuk Lintah Similar Early Childhood Education Unit. Based on a preliminary study of data from parents and teachers, most children experience language and speech problems due to lack of stimulation during children's language development. The results of the socialization illustrated that 10 people had sufficient parental knowledge and 7 people were good. From the results of this activity, the authors hope that parents will be able to identify early childhood speech and language development disorders. So that there are no problems in the next child's development process.